Application of Heuristics in Business Process Models to Support Software Requirements Specification - Nogueira, Fernando Aparecido [UNESP]; Oliveira, Hilda Carvalho de [UNESP]; Hammoudi, S.; Smialek, M.; Camp, O.; Filipe, J. (Scitepress, 2017)
Requirements Engineering has suffered difficulties caused by communication failures between business and Information Technology teams (IT). The knowledge of the enterprise's business domain is very important for the systems analysts when developing software solutions to automate activities and processes. However, these analysts come across frequent changes in the system scope and requirements descriptions incomplete or erroneous. This work presents a systematic process that takes into account the business process models to automatically extract functional and non-functional requirements, which compose the Software Requirements Specification document. This automatic process uses requirements heuristics implemented by a freeware software system that generates software requirements documents with use cases and UML diagrams. The systematic process uses XML to facilitate systems integration, as well the re-use and visualization of the results. Additionally, this work presents business heuristics that enable significant improvements in the documentation of the business process models, bringing advantages for the business and IT. Assessment tools for the level of documentation level are proposed for both the business process models as for software requirements documents.
Keywords: Requirements Engineering; Business Process Model; BPMN; XPDL; Heuristics; UML